1986
DOI: 10.1002/joc.3370060505
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of drought in the interior plains of North America

Abstract: A long-period data set (1975)(1976)(1977)(1978) of monthly growing season (April-September) rainfall totals for over 400 stations in the Interior Plains of North America is used to derive a Bhalme-and-Mooley-type drought index. A map-pattern correlation technique is used to stratify the time period into distinct drought severity patterns, and maps of the mean drought patterns for each year are generated by SYMAP and examined for consistency.Based on the analyses, there are four patterns of moisture anomaly wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The important spatial variability of droughts has been identified in several regions between neighbouring areas (Oladipo, 1986;Karl and Koscielny, 1982;Estrela et al, 2000;Bonaccorso et al, 2003). In the Iberian Peninsula, the differences in temporal evolution of droughts between regions are very important (Vicente- Serrano, 2006).…”
Section: Drought Spatial and Temporal Patterns During The Winter Seasonmentioning
confidence: 99%
“…The important spatial variability of droughts has been identified in several regions between neighbouring areas (Oladipo, 1986;Karl and Koscielny, 1982;Estrela et al, 2000;Bonaccorso et al, 2003). In the Iberian Peninsula, the differences in temporal evolution of droughts between regions are very important (Vicente- Serrano, 2006).…”
Section: Drought Spatial and Temporal Patterns During The Winter Seasonmentioning
confidence: 99%
“…Previous studies have found that preferred spatial patterns of moisture variability are often linked to a particular set of causal mechanisms (Oladipo, 1986;Nkemdirim and Weber, 1999). Therefore, the relationships between the main spatial modes of June-July moisture variability (as determined by the PCA) and a variety of atmospheric, oceanic, and surface-condition data were examined.…”
Section: Investigating Possible Causal Mechanisms Of Moisture Anomaliesmentioning
confidence: 99%
“…Past examinations of spatial and temporal extents of drought have been numerous (e.g., Skaggs, 1975;Klugman, 1978;Karl, 1983;McGregor, 1985;Oladipo, 1986;Soulé and Meentemeyer, 1989), while examinations of wet periods have been fewer in number (e.g., Diaz, 1983;Fye et al, 2003). Fye et al (2003) indicated that during the past 500 years only three pluvials may have equaled that of the early 20th century occurring from 1549-1558, 1602-1622 and 1825-1840.…”
Section: Introductionmentioning
confidence: 99%